Expression cloning of the pancreatic beta cell receptor for the gluco-incretin hormone glucagon-like peptide 1. - Thorens, B (1992)
Glucagon-like peptide 1 (GLP-1) is a hormone derived from the preproglucagon molecule and is secreted by intestinal L cells. It is the most potent stimulator of glucose-induced insulin secretion and also suppresses in vivo acid secretion by gastric glands. A cDNA for the GLP-1 receptor was isolated by transient expression of a rat pancreatic islet cDNA library into COS cells; this was followed by binding of radiolabeled GLP-1 and screening by photographic emulsion autoradiography. The receptor transfected into COS cells binds GLP-1 with high affinity and is coupled to activation of adenylate cyclase. The receptor binds specifically GLP-1 and does not bind peptides of related structure and similar function, such as glucagon, gastric inhibitory peptide, vasoactive intestinal peptide, or secretin. The receptor is 463 amino acids long and contains seven transmembrane domains. Sequence homology is found only with the receptors for secretin, calcitonin, and parathyroid hormone, which form a newly characterized family of G-coupled receptors.